Solventless synthesis of cerium oxide nanoparticles and their application in UV protective clear coatings. Issue 25 (14th April 2020) - Álvarez-Asencio, Rubén; Corkery, Robert W.; Ahniyaz, Anwar
Abstract : Solventless synthesis of metal oxide nanoparticles. Abstract : Colloidal dispersions of cerium oxide nanoparticles are of importance for numerous applications including as catalysts, chemical mechanical polishing agents and additives for UV protective and anticorrosion coatings. Here, concentrated oleate-coated cerium oxide nanoparticles (CeO2 NPs) with a uniform size have been produced by solventless thermolysis of cerium-oleate powder under low pressure at 320 °C and subsequently dispersed in hexane. Unlike any previously reported colloidal synthesis process for ceria nanoparticles, this process does not involve any toxic high boiling point organic solvent that requires subsequent removal at high cost. Although the process is very simple, highly concentrated cerium oxide nanoparticles with more than 17 wt% solid content and 70% of the theoretical yield can be easily obtained. Moreover, the size, shape and crystallinity of cerium oxide nanoparticles can be tailored by changing the thermal decomposition temperature and reaction time. Moreover, the new synthesis route developed in this study allows the synthesis of clean and dispersible ceria nanoparticles at a relatively low cost in a single step. The prepared ceria nanoparticles have an excellent UV absorption property and remain transparent to visible light, thus having the potential to replace potentially hazardous organic compounds in UV absorbing clear coatings. As a proof of concept, the prepared dispersions of cerium oxide nanoparticles in hexane were formulated into a solvent borne binder base to develop clear UV protecting coatings for light sensitive substrates. The general synthesis strategy presented in this study is generally applicable for the low-cost production of a concentrated dispersion of metal oxide nanoparticles with minimal environmental impact.